Sufism Hadith Perspective of Hadrotus Syaikh KH Hasyim Asy'ari: An Examination of the Book of Adabul Alim wa Muta'alim - Aizillalaa, Chicha; Sopingi, Imam; Syahiroh, Rima; Roshief, Muhammad 'Imaduddin (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
This article discusses hadith Sufism in the perspective of Hadrotus Shaykh KH. Hasyim Asy'ari by examining his monumental work, Adabul '?lim wa al-Muta'allim. This book is not only a guide to manners in the process of Islamic education, but also contains a Sufistic spiritual dimension based on the traditions of the Prophet Muhammad. Through a descriptive qualitative approach, this article examines how KH. Hasyim Asy'ari understood and internalized the values of Sufism in education through the interpretation of hadith. The emphasis on sincere intentions, control of lust, and spiritual closeness to Allah are the core of the Sufistic study. KH. Hasyim Asy'ari linked the traditions about knowledge with the practice of Sufism which is oriented towards tazkiyatun nafs (purification of the soul) and mahabbah (love of Allah and His Messenger). Thus, Sufism in his perspective is not only oriented to the inner aspects, but also integrated in the ethics of learning and teaching. This study shows that the book of Adabul '?lim wa al-Muta'allim reflects a harmonious blend of hadith scholarship and Sufistic spirituality, which is relevant to serve as a guide for Islamic character education today. [Artikel ini membahas sufisme hadis dalam perspektif Hadrotus Syaikh KH. Hasyim Asy’ari dengan menelaah karya beliau yang monumental, Adabul ‘?lim wa al-Muta‘allim. Kitab ini tidak hanya menjadi pedoman adab dalam proses pendidikan Islam, tetapi juga memuat dimensi spiritual sufistik yang berpijak pada hadis-hadis Nabi Muhammad SAW. Melalui pendekatan kualitatif deskriptif, artikel ini mengkaji bagaimana KH. Hasyim Asy’ari memahami dan menginternalisasi nilai-nilai sufisme dalam pendidikan melalui penafsiran hadis. Penekanan pada niat yang ikhlas, pengendalian hawa nafsu, serta kedekatan spiritual kepada Allah menjadi inti dari telaah sufistik tersebut. KH. Hasyim Asy’ari mengaitkan hadis-hadis tentang ilmu dengan praktik tasawuf yang berorientasi pada tazkiyatun nafs (penyucian jiwa) dan mahabbah (cinta kepada Allah dan Rasul-Nya). Dengan demikian, sufisme dalam perspektif beliau tidak hanya berorientasi pada aspek batin, tetapi juga terintegrasi dalam etika belajar dan mengajar. Kajian ini menunjukkan bahwa kitab Adabul ‘?lim wa al-Muta‘allim mencerminkan perpaduan harmonis antara keilmuan hadis dan spiritualitas sufistik, yang relevan untuk dijadikan pedoman pendidikan karakter Islami masa kini.]